Implementation of Integrated Marketing Communication Based on Purchase Intention in The Artisan Tea Marketing Program - Syahban, Khofifah Rahmat; Marsasi, Endy Gunanto (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study delves into a plantation industry company operating with B2B and B2C marketing but needs more digital marketing expertise. Their production base is situated in Wonosobo Regency, known for supplying raw materials to market leaders, positioning them as market followers. PT. Perkebunan Teh Tambi introduced the